Management approaches for primary hepatic lymphoma: 10 year institutional experience with comprehensive literature review - Ma, Jennifer; Daou, Remy; Bou Eid, Josiane; Fregonese, Beatrice; El-Khoury, Joe; Wijetunga, N. Ari; Imber, Brandon S.; Yahalom, Joachim; Hajj, Carla (Frontiers in Oncology, 2025)
Purpose/objectivePrimary hepatic lymphomas (PHL) are an extremely rare form of non-Hodgkin Lymphoma (NHL) for which there are no established treatment guidelines, with available literature largely comprised of small case reports. Therefore, we evaluate our institutional experience treating PHL within the context of existing literature to better understand treatment modalities, role of radiotherapy (RT), and outcomes.Materials/methodsWe conducted a single institutional retrospective study of all patients with PHL diagnosed from 2000-2021, defined as a biopsy-proven liver lesion in the absence of other lymphomatous solid organ involvement, except for concurrently diagnosed hepatosplenic lymphomas. Subgroup analysis was performed for diffuse large B-cell lymphoma (DLBCL) and indolent lymphomas, which included marginal zone lymphoma (MZL), Grade 1-2 follicular lymphoma (FL), and low-grade B-cell lymphoma (BCL), NOS. Univariable (UVA) and multivariable analysis (MVA) for overall survival (OS) were performed using the Cox proportional hazards model. A literature review was conducted using key words “liver”, “lymphoma”, and “treatment” to identify relevant literature.ResultsWe identified 30 patients with PHL within the institutional cohort and 192 patients from comprehensive literature review. Subgroup analysis of DLBCL included 15 patients. On MVA for OS, only ECOG score (p=0.02) and Lugano stage (p=0.04) remained significant. Subgroup analysis of the indolent lymphoma group included 9 patients. On MVA for OS, only age remained significant. Systemic therapy was the most common treatment modality overall (20 patients; 67%) with surgery, radiation and observation utilized in 4 patients (13%) each. Seventeen (57%) of patients were alive at the time of data collection, with 8 (27%) deceased and 5 (17%) lost to follow-up.ConclusionPHL are an extremely rare subtype of NHL for which there is no clear treatment consensus. Primary hepatic DLBCL appears to be treated mostly with chemotherapy with good disease control. For indolent PHL, low-dose RT appears to have good overall disease control with minimal toxicity. Our RT data is limited by the short duration of follow-up for patients receiving RT compared to those who received chemotherapy, surgery or observation. However, our results are encouraging for the use of RT for appropriate patients with indolent PHL.